2021
DOI: 10.4401/ag-8670
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Vulcanello based on the re-examination of historical sources (Vulcano, Aeolian Islands)

Abstract: The lava platform and the three pyroclastic cones of Vulcanello constitute the northernmost volcanic structure of the island of Vulcano (Aeolian Islands). The sandy isthmus connecting the platform to the main island was definitively formed in the first half of the 1500s; before then, Vulcano and Vulcanello were two close but separate islands. For a long time, the interpretation of the sources of the II-I century BC, had considered the islet as built up about 2200 years ago. This belief, which proliferated amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…The first of these islands is an uninhabited island called Vulcano that burns constantly day and night .” This is consistent with what was observed in the Palizzi and in Vulcanello 1 and 2 successions, associated to ash emissions (PAL A and PAL C, Vulcanello 1 and 2), more intense explosions with emplacement of pumice (PAL B and PAL D), and of lava flows, and also in agreement with age obtained by Malaguti et al ( 2022 ) for the onset of the PEU sequence. A further confirm of an important eruptive activity between the end of the tenth century and the twelfth century, when Vulcanello and Vulcano were still two separate islands, is presented in Manni and Rosi ( 2021 ), who suggest that the isthmus connecting the two islands formed later, in the sixteenth century AD.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…The first of these islands is an uninhabited island called Vulcano that burns constantly day and night .” This is consistent with what was observed in the Palizzi and in Vulcanello 1 and 2 successions, associated to ash emissions (PAL A and PAL C, Vulcanello 1 and 2), more intense explosions with emplacement of pumice (PAL B and PAL D), and of lava flows, and also in agreement with age obtained by Malaguti et al ( 2022 ) for the onset of the PEU sequence. A further confirm of an important eruptive activity between the end of the tenth century and the twelfth century, when Vulcanello and Vulcano were still two separate islands, is presented in Manni and Rosi ( 2021 ), who suggest that the isthmus connecting the two islands formed later, in the sixteenth century AD.…”
Section: Resultsmentioning
confidence: 90%
“…A small tuff rock (Il Faraglione) was possibly situated in the east sector of the bay. North of Il Faraglione, we hypothesize an area of shallow water, which extended northwards up to the area of the current Vulcanello for the presence of shallow seabed formed during the effusive activity of Roman times and continuously dismantled by marine erosion (Manni and Rosi 2021 ; Fig. 14 a).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…After observing the erosive processes following the 1888-90 eruption, De Fiore [27] reported that about 50 m of the slope were eroded between 1916 and 1921 [17]. The isthmus between Vulcanello and the Vulcano Porto plain (Figure 1) began to develop after the post-12th century emplacement of the Vulcanello lava platform [28,29]; it emerged from the sea due to both coastal processes and volcaniclastic sediment inputs from the La Fossa cone through the Vulcano Porto plain and the Palizzi Valley [30].…”
Section: Study Areamentioning
confidence: 99%